Exploring the national low-risk levels for alcohol consumption: a narrative review - Mahesh Rajasuriya; Yasara Manori Samarakoon (College of Community Physicians of Sri Lanka, 2021)
Introduction: Drinking guidelines are considered to help in minimizing the harms of alcohol use. Objectives: To review the current national guidelines on low-risk alcohol consumption (LRAC) and compare them to the latest evidence on risk thresholds for alcohol consumption Methods: We searched for, and then scrutinized, the national guidelines on LRAC issued by individual countries in the world through online database search and additional search via personal communication. The latest evidence of this scale on risk thresholds of alcohol consumption as presented in a major combined analysis authored by Wood et al. (2018) was used to analyse the appropriateness of the national LRAC guidelines found. We investigated the validity of this combined analysis communicating with the corresponding author when needed. Results: Forty-one countries have issued LRAC levels with a variation of390%, from 10 g up to 39 g/day for men. The definition of a standard drink has a variation of 250%, from 8 g to 20 g. The combined analysis by Wood et al. (2018), which showed features of a rigorous methodology combines data from 83 studies, revealing the positive relationship with the level of alcohol consumption and increased mortality even at levels of 100 g/week. Conclusions & Recommendations: The process of development of National LRAC Guidelines needs to be protected from the possibility of interference of the alcohol industry. In most cases, these national guidelines need to reduce the level recommended as per the Wood et al. (2018) fndings, which were found to be highly valid and accurate. Also, these LRAC guidelines should be specific and appropriately named.